Vous êtes sur la page 1sur 20

+ . = 0 = 1 i=1 = 0

0

A ” + ” . A

(A, +)

(A, .)

a, b, c A a.(b + c) = a.b + a.c (a + b).c = a.c + b.c . A (A, .) 1 A (A \ {0}, .) A

a A a (A, +) (A, +) a A a.0 = 0 0 = 1 A = {0} (G, +) (G) G G (G) (f + g)(x) = f (x) + g(x) (End(G), +, o) + (Z, +, .) (Q, +, .) (R, +, .) A A[X] A[X] A

i=0 n a i X i n N a i A P = 0 a i = 0

{i, a i = 0} n P a n = 0 P P = 0 −∞ 0 1

c i X i c i = k=0 i a k b ik a k b ik 0

( n

i=0 a i X i )( m

i=0 b i X i ) = n+m

i=0

A a A

a b A ab = 1

a 0 a

a n N a n = 0

= 0 b

= 0 ab = 0

1 0

= 0 0 a 0 A ×

a

A (A × , .)

A

A A

= {0} 0

A A 0

A A A

A B A B

1 B

a, b B, a b B

a, b B, a.b B

A B S A B[S] B B S

B[S]

finie b i s k 1 1

s

k

t

t

i

b i B s j S k l N

Z[i] C i 2 = 1

A B f : A −→ B f

a, b

A f (a + b) = f (a) + f (b)

a, b A f (a.b) = f (a).f (b)

f (1 A ) = 1 B f f

{0} A A

A {0} A

A B f : A −→ B f 1

A B f : A −→ B

f A × B ×

a A × b A × ab = 1 f (a).f (b) = 1 f (a) B × f (b)

A i i I iI A i iI A i

A A i i I π j iI A i A j A iI A i f i = π i f A A i i I

= {0}

A I A I A

(I, +) (A, +)

a A x I ax I

{0} A A I A

A I A

I

I A I = A ⇐⇒ 1 I ⇐⇒ ∃a A × , a I A {0} A

a, b I, a + b I I a I, x A, xa

⇐⇒ ∀a, b I,

x, y A,

xa + yb I

Z I Z I = nZ n N I nZ k I k[X] P [X] P I = P.k[X]

A (a i ) iI A S A (a i ) iI S J J = { k=1 n x k a i k n N x k A} J = { k=1 n x k s k n N x k A s k S}

A B f : A −→ B f (A)

Ker (f ) A

J B f 1 (J) A

I A f (I) f (A) B f

A f f = 0

A I J A

I + J = {x + y, x I, y J}

I.J S = {xy, x I, y J}

I J

A = Z a b 2 aZ + bZ = dZ d a b aZ bZ = mZ m a b aZ.bZ = abZ mZ

A 1 ,

A i

(a 1 ,

a i I i x i I π i (x i ) = a i (a 1 ,

0)x i I 1 i e

, a n ) I π i π i (I) = I i A i a i I i

, A n I i=1 n A i I 1 × ··· × I n I i

, a n ) = n i=1 (0,

, 1, 0

A a, b p A a b c A b = ac

a b u A × a = bu

p p / A × a, b A p = ab =a A × b A ×

a b (b) (a)

a 1 a A ×

a 1 a A ×

(a) = A a A ×

a

b (a) = (b)

p

p

= 0 (p)

p p

A = {0} p = 0 (p) = A p a (p) (a) a p p = ab p a

b A × p a (p) = (a)

A = Z/6Z p = 3 (3) 3 = 3.3 3

= 0 0 = 0.0 0 A ×

A = k[X, Y, Z]/(Z(1 XY )) a = Z b = ZX = aX Z = ZXY a = ZXY = bY U aU = b U, V R[X, Y, Z] Z(U X) = 0 (mod Z(1 XY )) ZX(V Y ) = 0 (mod Z(1 XY )) UV = 1 (mod Z(1 XY ))

R[X, Y, Z] Z = 0 A Z A d Z o P.Q = d o Z P + d Z o Q R[X, Y ]/(1 XY ) Z(X λ) = 0 A λ R

A a, b A a b (a, b) = A a b d a d b d

P, Q R R[X, Y, Z] U = X + (1 XY )P V

= Y + (1 XY )Q UV = 1 + Z(1 XY )R

A = R[X, Y ] a = X b = Y a b

A I A (A, +) I A (A/I, +)

A A/I

a b a = b + i i I c = d + j j I ac = bd + ia + jb + ij bd I ia I,

A I A I A/I + . A A A/I

A B f :

A −→ B A/ ker f −→ f (A)

f I A π A A/I f

¯

¯

f : A/I −→ B f = f π I ker f

ker f f (A) A/ ker f f (A)

¯

f f

A I A A I A/I

π A A/I π I A/I π A/I A I

A A A = {0} a, b A ab = 0 =a = 0 b = 0 A a n = 0 a = 0

A B f : A −→ B A

B

= {0} {0}

A

{0} ab = 0 a n = 0 f (ab) = f (a)f (b) = 0

f(a) n = 0 B f (a) f (b) f (a) = 0 f a b

A

(a) = (b) a b

a

= 0 ab = ac =b = c

p p

A[X]

ab = ac =a(b c) = 0 b c = 0 a =

(a) = (b) a = bu b = av u v A a = bu = avu a = 0 b = 0 0 = 0.1 a = auv uv = 1 a b

(p) p = ab a

= 0 (p)

0

(p) (a) (a)

= A (p) = (a) p a

p = ab = au u b = u d o A[X] \ {0} d o (P.Q) = d o (P) + d o (Q) A

A I I A/I I A/I I A/I

A {0}

A I

A {0} A {0} A {0} I I I I

I a A a n I =a I

I I

= A a, b A ab I =a I

b I

I I

1. 2. 3. 4. 5.

6. I a n I π A A/I π(a n ) = 0

A/I π(a) = 0 a I α A/I α = π(a) π(a n ) = 0

a n I

7. I I = A ab I π(a)(b) = 0 A/I

π(a) = 0 π(b) = 0 a I b I αβ = 0 A/I α = π(a) β = π(b) π

8. A I A/I

{0} I A/I I I I A/I {0} A/I x A/I x = 0 (x) = A/I x A/I

A I A I A/I π A A/I J I A/J (A/I)(J)

A −→ A/I −→ (A/I)(J) J J I

A B f : A −→ B I B

= A J I =J = A J = I

a b A ab f 1 (I) a n f 1 (I) f (ab) I f (a) n I I f (a) f (b) I f (a) I f (0)

A p A p

(p) p

= 0

(p) (p)

= A p p = ab ab (p)

a (p) a = pc p = ab = pbc b, c A A b c

A = Z[i 5] (i 5) 2 = 5 A C A

6 = 2.3 = (1 + i 5).(1 i 5) (2) (1 + i 5).(1 i 5) = 6 (2)

(1 + i 5) (1 i 5) (2) 2 2 2 = ab a, b A |a| 2 |b| 2 = 4 A 2 |a| 2 = 1 a = ±1

A I I I

I = {x A n N x n I}

I = {0} I A/I A I a x A ax a b a n = 0 b m = 0 n m (a + b) n+m = 0 a n (a n ) m = 0 a J a a n = 0 a n J J a J J I A/I

I I I

A/I I

A

I J = I J

I ⇐⇒ I = I

IJ = I J = I J

I ⊂ ∩p p I

I p I p

A (I i ) i={1, I i + I j = A π i A A/I i

x 1 ,

A = Z π i (x) = π i (x i ) x x i mod I i

n = 2 I 1 + I 2

π 1 (a 1 ) = 0 π 2 (a 1 ) = 1 a 2

= j =

,n}

i, j

, n}

∈ {1,

, n} i

x n A x A π i (x) = π i (x i ) i ∈ {1,

= A a 1 I 1 a 2 I 2 a 1 + a 2 = 1

x = x 2 a 1 + x 1 a 2

i < j a i,j I i a j,i I j a i,j + a j,i = 1 π i (a i,j ) = 0 π j (a i,j ) = 1 i = j (i, j) (j, i) a k = i =k a i,k a k I i i = k a i,k I i π i (a k ) = 0

π 1 (x) = π 1 (x 1 ) π 2 (x) = π 2 (x 2 )

= k π k (a i,k ) = 1 i =

i

k π k (a k ) = 1

x = k=1 n x k a k π k (x) = π k (x k ) k ∈ {1,

A (I i ) i={1,

I i + I j = A

A/ i=1 n I i −→ A/I 1 × · · · × A/I n

, n}

,n}

i, j ∈ {1,

, n} i

= j =

π i A A/I i f : A −→

A/I 1 × · · · A/I n f (x) = (π 1 (x), ··· , π n (x))

, n} = {x A x I i

i = 1,

ker f = {x A π i (x) = 0 i = 1,

, n} = n

i=1 I i

n

i=1 I i = n i=1 I i

I J I + J = A

n 1 φ(n) n φ(n) = Card(Z/nZ) ×

n 1 a ∈ {0,

a n aZ + nZ = Z

p n 1 φ(p n ) = (p 1).p n1

{a ∈ {0, p n 1} a p n }

A 1 ,

(A 1 × A 2 × ··· × A m ) × = A

f × : A × −→ B ×

n N n 2 n = p n 1

φ(n) = φ(p n 1 )

, n 1} a (Z/nZ) ×

, A m , A B f : A −→ B

×

1

× ··· × A

×

m

1

p

n m

m

p i n i > 0 p i = p j i

= j

φ(p n m )

m

1

A

S A S

1 S

a, b A a S b S =ab S

1 S S

S ∪ {1} 1

= S

S = A × I A \ I I = A 1 S 1 / I a b I I ab / I A S = A \ {0} {0} a A {a n , n N} a a n n < 0 a 0 = 1

S 1 A

A S A × S (a, s) (a , s ) s S (as a s)s = 0

(a 2 , s 2 )

(a 1 s 2 a 2 s 1 )s = 0 (a 2 , s 2 ) (a 3 , s 3 ) (a 2 s 3 a 3 s 2 )t = 0 s, t, s 1 , s 2 , s 3 S

(a 1 , s 1 ) (a 3 , s 3 )

a 1 s 2 ss 3 t

s 2 st S s (a 1 s 3 a 3 s 1 )s 2 = 0

(a 1 s 3 a 3 s 1 ) = 0

(a 1 , s 1 )

a 3 s 2 ts 1 s = 0 a 2 (a 1 s 3 a 3 s 1 )s 2 st = 0

A 0 / S (as a s)s = 0 as a s = 0

A S A×S

S 1 A A S A S (a, s) a/s a s

a/s = (at)/(st) t S 0 S a/0 S 1 A = {0} 0 a A s S (a, s) (0, 1) s = 0 S

A S S 1 A S 1 A

+ : S 1 A × S 1 A −→ S 1 A

. : S 1 A × S 1 A −→ S 1 A a . a

a/s + a /s = (as + sa )/ss

s

s

= aa /ss

0/1 a/s a/s 1/1

A S f A S 1 A f (a) = a/1 A S 1 A s S f (s) S 1 A A 0 / S f A f (A)

a/1 + b/1 = (a + b)/1 (a/1).(b/1) = ab/1 f (1) = 1/1 s S f (s) = s/1 1/s S 1 A f (s) f (a) = a/1 = 0 s S as = 0 A s S a = 0 f f

g : A −→ B S A s S g(s) B g˜ S